2018
DOI: 10.1001/jamadermatol.2017.4254
|View full text |Cite
|
Sign up to set email alerts
|

Firefighter Skin Cancer and Sun Protection Practices

Abstract: psoriasis. 3-5 Crude point estimates did not suggest an increased HZ risk in systemically treated patients with psoriasis, and we found no significant differences in HZ risk among those exposed to biologic vs nonbiologic therapy after adjusting for age and sex. Limitations. limitations of the study include lack of data on disease severity and potentially limited generalizability to other healthcare settings. Conclusions | Among a cohort of patients with moderate-tosevere psoriasis who were treated with a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
3
5
0
Order By: Relevance
“…Skin cancer was most prevalent amongst firefighters diagnosed with cancer after joining the Fire and Rescue Service (Fig. 1 ), mirroring international findings 23 26 . The most common cause of skin cancer is exposure to UV radiation 27 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Skin cancer was most prevalent amongst firefighters diagnosed with cancer after joining the Fire and Rescue Service (Fig. 1 ), mirroring international findings 23 26 . The most common cause of skin cancer is exposure to UV radiation 27 .…”
Section: Discussionsupporting
confidence: 64%
“…Skin cancer was most prevalent amongst firefighters diagnosed with cancer after joining the Fire and Rescue Service (Fig. 1), mirroring international findings [23][24][25][26] www.nature.com/scientificreports/ radiation 27 . Although the survey did not account for time spent working outdoors without protective clothing, firefighters who actively sunbathe/use sunbeds were not found to be at a significantly increased risk of cancer compared to those that never sunbathe (OR = 0.8, 0.6-1.0).…”
Section: Discussionsupporting
confidence: 58%
“…A higher risk of colorectal cancer was also observed in a 2006 meta-analysis of 32 studies on firefighters [ 5 ]. Several studies have also reported higher prevalence and risk of non-melanoma and melanoma skin cancer among firefighters [ 5 7 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ever receiving skin cancer screening in this study of volunteer firefighters (26.1%) was almost half that reported from a cross-sectional study of 2399 male career firefighters from Florida (47.3% screened). 12 Compared to the volunteer firefighters in our study, these career firefighters were similar in age but had fewer years of firefighting (14.7 years). 12 In both studies, the proportion of respondents using sunscreen and who perceived themselves as more likely to burn with prolonged sun exposure were similar.…”
Section: 0%mentioning
confidence: 55%